A framework for Satisfiability Modulo Theories. - Kroening, D; Strichman, O (2009)
We present a unifying framework for understanding and developing SAT-based decision procedures for Satisfiability Modulo Theories (SMT). The framework is based on a reduction of the decision problem to propositional logic by means of a deductive system. The two commonly used techniques, eager encodings (a direct reduction to propositional logic) and lazy encodings (a family of techniques based on an interplay between a SAT solver and a decision procedure) are identified as special cases. This framework offers the first generic approach for eager encodings, and a simple generalization of various lazy techniques that are found in the literature. © 2009 British Computer Society.